Penentuan ruang terbuka hijau (RTH) menggunakan drone dan analisis kesesuaian di Kecamatan Serang, Banten - Rahman, Aditya; Fitriani, Rika; Usman, Usman (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2024)
Serang District is the area with the largest population proportion but has the smallest area in Serang City. Population growth that is not accompanied by an increase in area will decrease the quality of the urban environment. Therefore, a city needs to provide Green Open Space (RTH) to balance the environment. The image quality will be better if you use UAV (Unmanned Aerial Vehicle) or drone technology to display RTH visualization. Thus, this study aims to determine public green space area using drones and analyze its suitability for green space needs based on the area and population in Serang District, Banten. This research is quantitative research with a descriptive approach and used the survey method. The results showed that Serang District has a public green open space of 108,348.81 m2 (0.41% of the area). Meanwhile the calculation results of the need for public green open space that must be met based on the area are 5,176,000 m², where 20% of total area and based on the population is 4,523,920 m². The urban areas in Serang District had not been able to meet the needs of green open space in terms of area and population.